LIMITATIONS OF WOMEN'S GENITALS ACCORDING TO M. SYAHRUR (Ijtihad Method Analysis Study) - Iqbal Dwi Syariansyah; Faisar Ananda; Jamil Jamil (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2021)
The formulation of the research problem is What are the limits of female genitalia according to M. Syahrur and How does M. Syahrur use the ijtihad method in determining the boundaries of female genitalia. This research is library research, using a reference source by M. Syahrur entitled al-Kitab wa al-Qur'anal-Qur'an Mu'ashirahMu'ashirah as the primary reference, as well as other books which include the issue of the boundaries of women'swomen's private parts. The results of the study show that the application of M. Syahrur'sSyahrur's limit theory (nazhariatul hudud) in the problem of the boundaries of women'swomen's private parts states that women cannot be naked because they exceed or exceed the minimum limit (al-hadd al-adnaa). The elements that must be covered and constitute genitalia for women are under the minimum limit (al-hadd al-adnaa), namely the lower part (al-juyub as-sufliyah), (al-juyub as-sufliyah) consisting of the genitals, buttocks, armpits, and breasts. The limitations of women'swomen's private parts in social activation in society include the minimum limits (al-hadd al-adnaa) and parts of women'swomen's bodies that must be covered per public perceptions. Women may not exceed the maximum limit (al-hadd al-a'la). Therefore, they cannot hide their face and hands, such as veiling (niqab). The ijtihad method used by M. Syahrur in determining the boundaries of women'swomen's private parts, with his theory Nazhariatul Hudud explains that there is a minimum limit (al-hadd al-adnaa) and a maximum limit (al-hadd al-a'laaal-a'laa). The minimum limit is the lowest provision of the rules prescribed by Allah SWT, while the maximum limit is the highest limit of a rule. Therefore, it is not permissible to do something less than the minimum limit and also not to do anything more than the maximum limit.Rumusan masalah penelitian ini adalah Apa saja batasan aurat perempuan menurut M. Syahrur dan Bagaimana metode ijtihad yang digunakan M. Syahrur dalam menentukan batasan aurat perempuan. Penelitian ini adalah penelitian pustaka (library research), dengan menggunakan sumber rujukan karya M. Syahrur berjudul al-Kitab wa al-Qur’an Mu`ashirah sebagai rujukan primer, serta kitab-kitab lainnya yang mencantumkan tentang masalah batasan aurat perempuan. Hasil penelitian menunjukkan bahwa Pengaplikasian teori limit (nazhariatul hudud) M. Syahrur dalam masalah batasan aurat perempuan menyebutkan bahwa perempuan tidak boleh telanjang, karena melebihi atau melampui dari batas minimal (al-hadd al-adnaa). Bagian-bagian yang wajib ditutupi dan merupakan aurat bagi perempuan sesuai dengan batas minimal (al-hadd al-adnaa), yakni bagian bawah (al-juyub as-sufliyah), (al-juyub as-sufliyah) terdiri dari kemaluan, pantat, ketiak, dan payudara. Batasan aurat perempuan dalam aktivasi sosial di masyarakatnya melingkupi batasan minimal (al-hadd al-adnaa), serta bagian dari tubuh perempuan yang harus ditutup sesuai dengan persepsi masyarakat. Perempuan Tidak boleh melampui batas dari batasan maksimal (al-hadd al-a`alaa), sebab itu tidak boleh menutup wajah dan dua telapak tangan, seperti bercadar (niqab). Metode ijtihad yang digunakan M. Syahrur dalam menentukan batasan aurat perempuan, dengan teorinya nazhariatul hudud menjelaskan bahwa ada batas minimal (al-hadd al-adnaa) dan batas maksimal (al-hadd al-a`laa). Batasan minimal, adalah ketentuan paling rendah dari aturan yang telah disyari`atkan oleh Allah SWT, sedangkan batas maksimalnya adalah batas paling tertinggi dari suatu aturan. Sebab itu, tidak dibolehkan melakukan sesuatu kurang dari batas minimal dan juga tidak boleh melakukan sesuatu melebihi dari batas maksimal